Analisis Yuridis Reforma Agraria dan Tata Ruang Paska Pengesahan Masyarakat Adat Rungan - Yesiska, Yesiska; Nugroho, Meysita Arrum (Neolectura, 2025)
Indigenous law communities are people who have inhabited an area for generations, with characteristics, rules, and structures that differ from other indigenous communities. The existence of indigenous communities in Indonesia existed long before Indonesia's independence, and they have independent legal institutions that are used to regulate the lifestyle and behaviour of each member of their community or those in the area where they live. They are the real actors behind preserving nature and the environment. The role of indigenous communities is very large, but currently, recognition of their existence is still quite weak. Recognition of the rights of indigenous peoples to the environment has been normatively stated after Indonesia's independence. This recognition is contained in legislation, the content of which is to emphasize the role of indigenous communities in regulating nature and everything in it for the benefit of each other and the state. Legislation has firmly emphasized the role of Indigenous peoples in nature and everything in it long before they had legal recognition as Indigenous Law Communities (MHA) or special legislation which is still far from being passed. The purpose of this research and journal writing is to examine juridically the agrarian reform and spatial planning after the ratification of Indigenous Law Communities (MHA) in the Basic Agrarian Law (UUPA).